Aaron Harber correspondence - Harber, Aaron, 1838-
Chiefly letters written from Carver Hospital (Carver General Hospital), Washington, D.C., by Harber of the 105th Ohio Infantry Regiment to his wife Nancy Almina "Mina" Harber relating primarily to personal affairs including his military pay and regimental matters. One letter includes a note to Elisabeth H. Warren. Also includes a letter (1858 May 23; Dorset Ohio) from Harber to Mina prior to their marriage, a letter (1864 December 11) of Mina Harber to Aaron Harber, and an 1865 letter to Mina from her friend, Emily F. Warren, of Jefferson, Ohio, discussing local and family news.
Union Army soldier.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Harber, Nancy Almina -- Correspondence; Warren, Elisabeth H. -- Correspondence; Warren, Emily F. -- Correspondence; Carver General Hospital (Washington, D.C.); United States. -- Army -- Pay, allowances, etc; United States. -- Army. -- Ohio Infantry Regiment, 105th (1862-1865); Jefferson (Ashtabula County, Ohio) -- History; Ohio -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; Washington (D.C.) -- History -- Civil War, 1861-1865.; Soldiers